Smart Teacher di Era Digital: Penguatan Kompetensi TPACK pada Guru JSDI Aceh Timur - Muhammad Khalil; Hasby Hasby; Okhaifi Prasetyo (Universitas Muhammadiyah Semarang, 2024)
This community service activity aims to increase TPACK (Technological Pedagogical Content Knowledge) competency among teachers who are members of the Indonesian Digital School Network (JSDI) in East Aceh. Through a series of stages that include planning, implementing education and workshops, as well as evaluation, the results show a significant increase in teachers' understanding and skills regarding the TPACK concept. Teachers are able to integrate technology in learning effectively, supporting the implementation of the Independent Curriculum. Evaluation shows an increase in the average score from pre-test to post-test by 41.6%. Collaboration between the service team from Samudra University and JSDI East Aceh partners strengthens the effectiveness of this program. Despite facing challenges such as technological skills gaps and limited facilities, the solution implemented is in the form of individual assistance and the provision of simple but effective technological alternatives. Sustainability of this program is sought through regular mentoring and additional training. This activity emphasizes the importance of a needs-based approach, ongoing support, and effective collaboration to improve the quality of education. With strong commitment from all parties, it is hoped that the Smart Teacher concept can be realized, creating a learning environment that is more innovative, inclusive and adaptive to changing times.